Tinjauan Dogmatis mengenai Pemahaman Jemaat GKPI Jemaat Khusus Pandumaan tentang Parousia Kristus sebagai Suatu Kebangkitan bagi Manusia (International Forum of Researchers and Lecturers, 2025)
This study aims to provide a new understanding for people who are interested in the parousia of Christ as the resurrection of man. The location of this study was at the GKPI Jemaat Khusus Pandumaan, and used a mixed method, namely quantitative, distributing questionnaires to randomly selected respondents, and qualitative, interviewing people who were considered qualified by the researcher. It is interesting that the congregation of the GKPI Jemaat Khusus Pandumaan believes that the parousia of Christ will occur but they do not understand what its function is for them, both between the relationship between the parousia of Christ and the resurrection of man from the dead in the future. Referring to a conclusion, the Parousia of Christ is a resurrection for man because after man dies the flesh and spirit are separated and then the spirit stops until the parousia takes place, then the dead man is resurrected. So to every local church, especially the pastor who functions as the leader of the church, to study this teaching more deeply so that church members know the meaning and purpose of the parousia of Christ.